Urinary phthalate metabolites, coronary heart disease, and atherothrombotic markers - Su, Ta-Chen; Hwang, Juey-Jen; Sun, Chien-Wen; Wang, Shu-Li (Ecotoxicology and environmental safety, 2019)
Cross-sectional studies have described an association between exposure to phthalate esters and cardiovascular risk factors. However, the association with coronary heart disease (CHD) is still unclear. A total of 180 subjects randomly selected from 336 CHD patients, and 360 age- and sex-matched non-CHD controls were included from 2008 to 2011. Urinary metabolites of phthalate esters were measured by liquid chromatography–tandem mass spectrometry. The geometric means of urinary phthalates metabolites were significantly higher for the three Di-(2-ethylhexyl)-phthalate (DEHP) metabolites, mono‐2‐ethylhexyl phthalate (MEHP), mono‐(2‐ethyl‐5‐hydroxyhexyl) phthalate, and mono‐(2‐ethyl‐5‐oxohexyl) phthalate among CHD patients in-hospital than those of being discharged. Excluding 89 CHD patients of in-hospital and hospital discharge within 2 days, we found the urinary concentrations of MEHP, mono‐n‐butyl phthalate (MnBP), and mono-isobutyl phthalate (MiBP) of 91 CHD patients discharged ≥ 3 days were higher than those of controls. Among 451 participants, those with higher tertile levels of urinary MEHP, MnBP, and MiBP showed an increased risk for CHD compared to those with lowest tertile levels; the corresponding odds ratios (95% CI) were 2.77 (1.22–6.28), 2.90 (1.32–6.4), and 3.19 (1.41–7.21), respectively, after adjustment for confounders. Higher levels of hs-CRP, fibrinogen, and D-dimer were linked with increased levels of all DEHP metabolites in CHD patients. In conclusion, exposure to DEHP and dibutyl phthalates was positively associated with CHD and this relationship may be probably mediated via atherothrombosis. Data was adjusted for age, gender, body mass index, diabetes mellitus, hypertension, and hypercholesterolemia, use of statins, smoking, and alcohol consumption according to tertiles of urinary phthalate levels. [Display omitted] •Urinary MEHP, MiBP, and MnBP are associated with coronary heart disease (CHD).•DEHP metabolites are associated with hs-CRP, fibrinogen, and D-dimer in CHD patients.•Regulation to reduce phthalates exposure, particularly DEHP and DBP, is important.•The mechanism of phthalates exposure and CHD awaits further investigations.